Sumbangsih Pemikiran John Hick: Teologi Misi Dalam Pluralisme Agama Di Indonesia - Edy Leonardo Hutahaen; Nancy Frisca Lumban Tobing (Mitra Sriwijaya: Jurnal Teologi dan Pendidikan Kristen, 2023)
This article wrote about the attitude of Christianity in relation to other religions. The attitude in question is an act or act of acceptance or rejection of those who are of a different religion with Christians. Based on the thoughts of John Hick, through the experience of interreligious relations, the author describes his theological understanding in a settings of God’s mission which is applied through interactive dialogue. Because John Hick tends to direct Christians to build religious pluralism, not to be exclusive or inclusive. The literature approach through several books written by John Hick, the author finds as a valuable contribution to be preservation of religious tolerance in Indonesia. John Hick directs our way of thinking and relating as an attitude of tolerance that is opened and free to every religion without any intervention and the interests of certain groups.